The Effect of Circuit Training Method on Leg Muscle Explosive Power - Yuliandra, Rizki; Nugroho, Reza Adhi; Gumantan, Aditya (Department of Physical Education, Sport, Health and Recreation, 2020)
The purpose of this research was to determine the effect of circuit training method on the leg muscle explosive ability. In this circuit training 4 posts containing exercises for strength and speed were designed. The research method used was experimental research. There were 24 research subjects divided into 2 groups, 12 in the treatment group and 12 in the control group using random sampling method. To obtain the data, pre test and post test were conducted in the treatment group and the control group using vertical jump test instrument. To ensure that this data were normally distributed, a normality test was carried out using the Kolmogorov Smirnov test. The results of this study showed a significant increase in the treatment group by 6.49. Post test data that has been tested through the t test (independent samples test) showed a P value < of a, that is 0.008 < 0.05 which means that the post test results had a significant increase compared to the control group. This circuit training method that contains strength and speed training can improve leg muscle explosive power.